2016
DOI: 10.1063/1.4948305
|View full text |Cite
|
Sign up to set email alerts
|

The evolution mechanism of defect dipoles and high strain in MnO2-doped KNN lead-free ceramics

Abstract: Defect dipoles in acceptor-doped (K0.5Na0.5)NbO3-based ceramics have a significant influence on their electrical properties. The present study examined the influence of the sintering atmosphere on the electrical properties of MnO2-doped (K0.5Na0.5)NbO3. The poled and aged samples sintered in the Ar atmosphere depicted unusual behavior related to the formation of defect dipoles (Mn2+Nb‴−VO··)′, aligned in the poling direction having larger polarity. The S-E loop of the poled and aged MnO2-doped (K0.5Na0.5)NbO3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 27 publications
5
47
0
Order By: Relevance
“…In addition, it is worth noting that the bipolar S‐E curves for both samples are asymmetrical (Figure A,B), indicating that there are some defects existed in these ceramics due to the volatility of A‐site alkali metal ions during high temperature sintering process. Compared with the random ceramics, the S‐E curves of the textured samples show greater asymmetry, which is attributed to more defect dipoles formed by A‐site vacancy and oxygen vacancy after aging with longer sintering time . Similar results have also been observed in {[Bi 0.5 (Na 0.84 K 0.16 ) 0.5 ] 0.96 Sr 0.04 }(Ti 0.075 Nb 0.025 )O 3 ceramics system .…”
Section: Resultssupporting
confidence: 69%
“…In addition, it is worth noting that the bipolar S‐E curves for both samples are asymmetrical (Figure A,B), indicating that there are some defects existed in these ceramics due to the volatility of A‐site alkali metal ions during high temperature sintering process. Compared with the random ceramics, the S‐E curves of the textured samples show greater asymmetry, which is attributed to more defect dipoles formed by A‐site vacancy and oxygen vacancy after aging with longer sintering time . Similar results have also been observed in {[Bi 0.5 (Na 0.84 K 0.16 ) 0.5 ] 0.96 Sr 0.04 }(Ti 0.075 Nb 0.025 )O 3 ceramics system .…”
Section: Resultssupporting
confidence: 69%
“…Its d33 decreases first at 25‐100°C, then increase at 100‐190°C, finally decrease sharply again. The spontaneous polarization P s could be switched toward the direction of the applied electric field to generate an electro‐strain due to the switch and extension of P s . However, there is an interaction between defect dipoles and spontaneous polarization P s inside domains .…”
Section: Resultsmentioning
confidence: 99%
“…The spontaneous polarization P s could be switched toward the direction of the applied electric field to generate an electrostrain due to the switch and extension of P s . 50,51 However, there is an interaction between defect dipoles and spontaneous polarization P s inside domains. 46 The defect dipole ðMn 00 Zr À V :: o Þ in the poled (35 kV/cm)/aged (3 days) Mn 0.8 ceramics must be negative to the extension of P s .…”
Section: Airmentioning
confidence: 99%
“…The IR of the 0.2 mol% Mn‐doped ceramic is 24.9 × 10 12 Ω/cm, which is the highest among all of the Mn‐doped ceramics. It has been reported that MnO 2 can convert to diverse valence states when heated: MnO2false⟶535CMn2normalO3false⟶1080CMn3normalO4false⟶1650CMnO…”
Section: Resultsmentioning
confidence: 99%